Pengaruh penggunaan model pembelajaran cooperative learning type team assisted individualiztion terhadap hasil belajar Matematika siswa kelas III Sekolah Dasar - Tuti Faoziah; Irfan Fajrul Falah (COLLASE (Creative of Learning Students Elementary Education), 2026)
This Study aims to determine the effect of the cooperative learning model type TAI (Team Assisted Individualization) on the learning outcomes of third-grade students of SDN 1 Jalaksana. The type of research used is experimental research with the design used is Quasi-experimental and the design form is non-equivalent control group design. The instrument used in this study is a student learning outcome test (pre-test and post-test), the test used is an essay of 10 questions that have been tested for validity and reliability. The research sample taken is all third-grade students of SDN 1 Jalaksana. The average mathematics learning outcomes of third-grade students in the experimental class post-test are 85.86 and the control class post-test score is 71.89. Description of research data from post-test data analysis using the independent sample test shows a significance value of 0.000 <0.5. From the provision criteria if significance <0.5 then Ho is rejected Ha is accepted. Thus, it can be concluded that the implementation of the Team Assisted Individualization (TAI) learning model significantly influences mathematics learning outcomes in third-grade elementary school students.   Keywords : Learning outcomes, Learning model, TAI.